2012
DOI: 10.1007/s00405-012-2036-1
|View full text |Cite
|
Sign up to set email alerts
|

Laryngeal electromyography: a proposal for guidelines of the European Laryngological Society

Abstract: Although recognized as a valuable diagnostic tool for more than 60 years, many laryngologists do not routinely use laryngeal electromyography (LEMG). This may be due to a persisting lack of agreement on methodology, interpretation, validity, and clinical application of LEMG. To achieve consensus in these fields, a laryngeal electromyography working group of European neurolaryngologic experts was formed in order to (1) evaluate guidelines for LEMG performance and (2) identify issues requiring further clarificat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
70
0
15

Year Published

2013
2013
2017
2017

Publication Types

Select...
10

Relationship

5
5

Authors

Journals

citations
Cited by 97 publications
(85 citation statements)
references
References 35 publications
0
70
0
15
Order By: Relevance
“…It requires technical equipment as well as specialised knowledge of methodology and interpretation. Furthermore, its validity and clinical application is still questionable within human medicine (Volk et al 2012). Change in NGGA has been applied in few studies investigating the effect of anaesthetic protocols on laryngeal examination in healthy animals , Nelissen et al 2012.…”
Section: Discussionmentioning
confidence: 99%
“…It requires technical equipment as well as specialised knowledge of methodology and interpretation. Furthermore, its validity and clinical application is still questionable within human medicine (Volk et al 2012). Change in NGGA has been applied in few studies investigating the effect of anaesthetic protocols on laryngeal examination in healthy animals , Nelissen et al 2012.…”
Section: Discussionmentioning
confidence: 99%
“…12,13 Currently, LEMG is being widely used to identify presbylarynx of paresis 14 and to study the severity of dysphagia, 15 but it needs to be compared across studies before being incorporated into standard procedures as proposed by the Working Group on Neurolaryngology of the European Laryngological Society. 16,17 …”
Section: Discussionmentioning
confidence: 98%
“…Later the Neurolaryngology Study Group of the American Academy of Otolaryngology –Head and neck Surgery conducted a further review and found that laryngeal EMG could only be used for qualitative EMG (Blitzer, Crumley, Dailey, et al, 2009). The European Laryngological Society provided a description of the methods and techniques currently available for laryngeal electromyography and recommended workshops be provided to provide training for larynoglogists on its use in clinical practice for diagnosis of superior laryngeal nerve injury (cricothyroid muscle) and recurrent laryngeal nerve injury (the thyroarytenoid muscle)(Volk, Hagen, Pototschnig, et al., 2012). As follow-up the use of a training workshop for allowing practitioners to develop skills in the practice and interpretation of laryngeal EMG showed encouraging results indicating improved reliability with training (Volk, Pototschnig, Mueller, et al, 2015).…”
Section: Laryngeal Reflexesmentioning
confidence: 99%